New Mediterranean Biodiversity Records (October, 2014) - S. KATSANEVAKIS; Ü. ACAR; I. AMMAR; B. A. BALCI; P. BEKAS; M. BELMONTE; C. C. CHINTIROGLOU; P. CONSOLI; M. DIMIZA; K. FRYGANIOTIS; V. GEROVASILEIOU; V. GNISCI; et al. (Mediterranean Marine Science, 2014)
The Collective Article ‘New Mediterranean Biodiversity Records’ of the Mediterranean Marine Science journal offers the means to publish biodiversity records in the Mediterranean Sea. The current article is divided in two parts, for records of alien and native species respectively. The new records of alien species include: the red alga Asparagopsis taxiformis (Crete and Lakonicos Gulf) (Greece); the red alga Grateloupia turuturu (along the Israeli Mediterranean shore); the mantis shrimp Clorida albolitura (Gulf of Antalya, Turkey); the mud crab Dyspanopeus sayi (Mar Piccolo of Taranto, Ionian Sea); the blue crab Callinectes sapidus (Chios Island, Greece); the isopod Paracerceis sculpta (northern Aegean Sea, Greece); the sea urchin Diadema setosum (Gökova Bay, Turkey); the molluscs Smaragdia souverbiana, Murex forskoehlii, Fusinus verrucosus, Circenita callipyga, and Aplysia dactylomela (Syria); the cephalaspidean mollusc Haminoea cyanomarginata (Baia di Puolo, Massa Lubrense, Campania, southern Italy); the topmouth gudgeon Pseudorasbora parva (Civitavecchia, Tyrrhenian Sea); the fangtooth moray Enchelycore anatine (Plemmirio marine reserve, Sicily); the silver-cheeked toadfish Lagocephalus sceleratus (Saros Bay, Turkey; and Ibiza channel, Spain); the Indo-Pacific ascidian Herdmania momusin Kastelorizo Island (Greece); and the foraminiferal Clavulina multicam erata (Saronikos Gulf, Greece). The record of L. sceleratus in Spain consists the deepest (350-400m depth) record of the species in the Mediterranean Sea. The new records of native species include: first record of the ctenophore Cestum veneris in Turkish marine waters; the presence of Holothuria tubulosa and Holothuria polii in the Bay of Igoumenitsa (Greece); the first recorded sighting of the bull ray Pteromylaeus bovinus in Maltese waters; and a new record of the fish Lobotes surinamensis from Maliakos Gulf.

New Mediterranean Biodiversity Records (December 2012) - M. THESSALOU-LEGAKI; O. AYDOGAN; P. BEKAS; G. BILGE; Y.O. BOYACI; E. BRUNELLI; V. CIRCOSTA; F. CROCETTA; F. DURUCAN; M. ERDEM; A. ERGOLAVOU; H. FILIZ; et al. (Mediterranean Marine Science, 2012)
This paper presents records extending or confirming the distribution of Mediterranean species. Three alien algae are included, namely Codium taylorii reported for the first time from the Aegean and Turkey (Izmir Gulf), Caulerpa racemosa var. cylindracea (Karpathos and Chalki Isl., Aegean Sea) and Ganonema farinosum (Karpathos Isl., Aegean Sea). As far as animals are concerned, Litarachna divergens (Acari: Hydrachnidia) was recorded (Side, Eastern Mediterranean) and represents a new amendment at genus level for Turkish fauna. Other invertebrates include alien species such as the crabs Dyspanopeus sayi (Lago Fusaro, SW Italy), Percnon gibbesi (Larnaca, Cyprus; Karpathos and Chalki Isl., Aegean Sea) and Callinectes sapidus (Voda estuary, NW Greece), the nudibranch Aplysia dactylomela (Boka Kotorska Bay, Montenegro), the gastropod Conomurex persicus (Karpathos and ChalkiIsl., Aegean Sea) and the bryozoan Electra tenella (Livorno harbour and Messina Straits area). The alien fish Siganus luridus, Siganus rivulatus, Fistularia commersonii, Sphyraena chrysotaenia and Sargocentron rubrum are also reported from the islands of Karpathos and Chalki, and Pteragogus pelycus from Heraklion Bay, Crete. In addition, new localities for four rare Mediterranean inhabitants are given: the cephalopod Thysanoteuthis rhombus (NW Sardinia) and the fish: Lampris guttatus (Calabria, S Italy), Petromyzon marinus (Gokova Bay) and Remora australis (Saronikos Gulf), while the opisthobranch gastropod Cerberilla bernadettae is reported for the first time from the E Mediterranean (Cyprus). Finally, three species of the Aegean ascidiofauna are recorded for the first time: Lissoclinum perforatum, Ciona roulei and Ecteinascidia turbinata. Furthermore, it was established that Phallusia nigra has extended its distributional range to the north of the Aegean Sea.

Variability of environmental factors of an eastern Mediterranean Sea river influenced coastal system - K.AR. KORMAS; A. NICOLAIDOU; M. THESSALOU-LEGAKI (Mediterranean Marine Science, 2003)
Spercheios River discharge rates of nutrients, suspended particulate matter (SPM) and particulate organic carbon (POC) and seawater concentrations of these parameters as well as chlorophyll a(chl a) were measured in the Maliakos Gulf, Greece, on a monthly basis between 1992-1993. From all the nutrients measured, silicate showed the highest discharge rates followed by nitrate, phosphate and nitrite. The river introduced significant amounts of SPM (8.5 – 35.5 Kg d -1 ) with very low POC content (

Facultative lecithotrophy during larval development of the burrowing shrimp Callianassa tyrrhena (Decapoda: Callianassidae) - M. Thessalou-Legaki; A. Peppa; M. Zacharaki (Marine Biology, 1999)

Estimation of the reproductive output of the burrowing shrimp Callianassa tyrrhena : a comparison of three different biometrical approaches - M. Thessalou-Legaki; V. Kiortsis (Marine Biology, 1997)